Business Process re-engineering to support the sustainability of the construction industry and sales commodities in large scale transaction during Covid 19 with integrating ERP and Quotation System - Budiman, Kholiq; Subhan, Subhan; Efrilianda, Devi Ajeng (Universitas Negeri Semarang, 2021)
Covid 19 has become a pandemic that has hit all over the world. Almost all sectors are affected by this pandemic, not only in the health sector. The economic and industrial sectors have also suffered severe impacts due to the coronavirus pandemic. This spreading virus does not support economic growth either nationally or globally. Finally, it has an impact on various industrial sectors in the country, from manufacturing to finance. The industry was one of the largest contributors to Indonesia's Gross Domestic Product (GDP) last year. The contribution given from this industry to the 2019 GDP was recorded at 19.62%. Due to this pandemic, according to the Central Statistics Agency (BPS), during February 2020, the importance of all categories of goods decreased compared to January 2020. This stunted industrial development was due to the government's appeal for social distancing; social distancing made it difficult for industry players to make transactions. Several obstacles require re-engineering of business processes in the industry. In general, the industry already has an Enterprise Resource Planning (ERP) system used in the related production process. However, ERP does not enter into the realm of buying and selling or the process of procuring goods with consumers. Therefore we need a Business Process Reengineering as an engineering process to integrate the ERP and the bidding system or quotation system. Using the moving average method as a forecasting method, we can get sustainable sales even during the Covid period, even seen an increase in transactions in the new period, along with the implementation of the quotation information system applied in the re-engineering business process.